فعالية تطبيق نموذج التعليم PAIR CHECK بالطريقة السمعية الشفهية لترقية مهارة الإستماع والكلام لطلاب الفصل الثامن بمدرسة دار العلوم المتوسطة الإسلامية وارو سدووارجو - Kholifah, Siti Nur; Nu’man, Muhammad (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
The process of learning Arabic in MTS Darul Ulum Sidoarjo is still traditional and students find it difficult to understand subject matter especially listening ' and speaking. The purpose of this study are: (1) To find out the special skills and greetings of students of class VIII at MTs Darul Ulum Sidoarjo. (2) To find out the application of the PAIR CHECK model "by using the syam’iyyah syafahiyyah method to improve listening and speaking skills. (3) To find out the effectiveness of the " PAIR CHECK "model by using the syamiyyah syafahiyyah method to improve listening and speaking skills. The Results from this research is: the "PAIR CHECK" model using the syamiyyah syafahiyyah method to improve this skills is effective in improving listening and speaking skills' with with a t-count = 15 and writing skills with a t-count = 17. Hypothesis results using the T-test symbol indicate that t count > ttable means that the null hypothesis (Ho) is returned and the hypothesis (Ha) can be accepted.